Український метанаратив: нелінійність та дискретність історії - Андрєєв, В. (Інститут історії України НАН України, 2008)
The article considers nonlinearity opinions on the history of Ukraine. The author analyzed the original conception of “volte -face” and discontinuity of the historical time by V.Petrov and reconstructed thinker’s views on history of Ukraine.